Resistance to Cyclic Fatigue of Nickel-Titanium Files Immersed in Sodium Hypochlorite at Body Temperature - Hind F. Abuhulaibah; Ammar AbuMostafa (International Journal of Dentistry)
Background/purpose. To assess the resistance to cyclic fatigue (CF) displayed by two nickel-titanium (NiTi) files, One Curve (OC) and ProTaper Gold (PTG), after their immersion in 2.5% sodium hypochlorite (NaOCl) solution at body temperature. Materials and Methods. Forty-five files from each brand were randomly assigned to three groups (n = 15) and subjected to the following: no immersion (control), 1-minute immersion, and 5-minute immersion in 2.5% NaOCl at 37°C. CF for all the files was tested within a well-lubricated stainless-steel artificial canal in a water bath at 37°C simulating body temperature. The procedure was video recorded, and the number of cycles to fracture (NCF) was calculated by multiplying the time taken to fracture, with the number of rotations per second. The data were analyzed for normality, and thereafter, one-way ANOVA with multiple Bonferroni was used as the post hoc test. Results. The resistance to CF of OC files was significantly higher than PTG files in all groups. In groups immersed in NaOCl for one minute, OC files showed significant drop in the CF resistance; PTG files showed a drop as well but not significantly. Both files demonstrated a significant drop in resistance to CF after immersion in NaOCl for five minutes compared to the control group. Conclusion. OC files were significantly more resistant to CF compared to PTG in all groups. Immersion in 2.5% NaOCl for 5 minutes significantly reduced the resistance to CF for all the files.